Availability and Pricing of Orthobiologic Knee Injections Vary by Practice Type but Not by Community Socioeconomic Vulnerability in Suburban New York - Tracy M. Tauro; Benjamin Hershfeld; Katharine Chen; Ran Lampert; Adam D. Bitterman; Randy M. Cohn; Nicholas A. Sgaglione (Arthroscopy, Sports Medicine, and Rehabilitation, 2026)
Purpose To assess the availability, price transparency, and pricing of platelet‐rich plasma (PRP), bone marrow aspirate concentration, and stem cell injections for knee osteoarthritis (OA) among orthopaedic sports medicine (OSM) practices and alternative clinics in suburban New York and to evaluate the impact of the economic status of a population on the availability and pricing of biologic injections. Methods Between July and September 2025, OSM practices and alternative clinics offering PRP, bone marrow aspirate concentration, or stem cell injections for knee OA were identified through American Orthopaedic Society for Sports Medicine and Arthroscopy Association of North America databases and web searches. Clinics were contacted using a standardized telephone script. Analyses used Mann‐Whitney U, Fisher's exact, and Levene's tests. Associations with socioeconomic vulnerability were evaluated using the Social Vulnerability Index and Spearman correlation. Results Seventy‐six (50 OSM, 26 alternative) of 91 clinics offered orthobiologics. PRP availability was similar between groups (98% vs 92%; P = .488), whereas stem cell injections were more common at alternative clinics (38% vs 6%; P < .001) and bone marrow aspirate concentration was rare (0% vs 4%; P = .329). PRP price disclosure was similar (84% vs 85%; P = .99). Median PRP price was $1000 for OSM and $875 for alternative clinics ( P = .059). Median stem cell price was $3500 at alternative clinics versus $750 at the single OSM listing ( P = .056). Clinic location vulnerability did not differ by provider type, and PRP price was not correlated with Social Vulnerability Index. Conclusions Orthobiologic injections for knee OA are widely available in suburban New York. PRP is nearly universal, stem cell injections remain concentrated in alternative clinics, and pricing is unrelated to community socioeconomic vulnerability. Clinical Relevance Orthobiologic injections for knee OA are broadly available in suburban practice settings, with variable pricing and transparency that have implications for patient counseling and shared decision‐making in an out‐of‐pocket market with limited clinical evidence.